THE ROLE OF BRAND IMAGE, BRAND TRUST, AND INTIMACY ON CONSUMER COMMITMENT - Riska K; Salju Salju; Goso Goso; Rahmawati Rahmawati; Junaidi Junaidi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The restaurant products quality issues have emerged in some developing countries. This research investigates how restaurant brand image and brand trust influencing consumers’ intimacy, subsequently mediates the relationship between brand image and brand trust as predictor on consumers’ commitment. The sample consists of 107 consumers obtained through an online survey. Structural Equation Modeling (SEM) was used to examine the research hypotheses. The empirical results indicate that brand image and brand trust have significant and positive effects on consumers’ intimacy. Furthermore, as mediator variable, consumers’ intimacy play important role in mediates the relationship between brand image and brand trust on consumers’ intimacy. This study was validated Indonesian restaurant consumer or food firlds, therefore, future study is required to analyze across the culture, region and sector. It can help restaurant managers and scholars to observe the correlation between brand image and consumers’ behavior. The current study provided enlighten the consumers’ principal operation from the perspective of marketing. Moreover, this study can be a reference for the government and culinary tourism business owners in an effort to increase consumer commitment and sustainable growth of the restaurant sector.